Complete chloroplast genome analysis of Hypopterygium flavolimbatum Müll. Hal. (Hypopterygiaceae, Bryophyta) - Zheng-Kai Ye; Guo-Yong Yang; Ye Tang; Qin-Yu Liu; Li-Hua Chen; Xiang-Hua Fang (Mitochondrial DNA. Part B. Resources, 2025)
To address limited genomic resources hindering Hypopterygium phylogenetics/taxonomy, the chloroplast genome of Hypopterygium flavolimbatum Müll. Hal. (Hypopterygiaceae, Bryophyta) was sequenced. The chloroplast genome is 125,283 bp in length, comprising an 86,845 bp large single-copy region, an 18,606 bp small single-copy region, and a pair of 9916 bp inverted repeats. A total of 127 genes were predicted, including 82 protein-coding genes, 36 tRNA genes, and 8 rRNA genes. Phylogenetic analysis indicates that H. flavolimbatum exhibits the closest genetic affinity with a clade containing Myurella julacea, Myuroclada maximowiczii, and Climacium dendroides. This study provides essential sequence data for species identification and phylogenetics.